The German language in the town council of Cracow in 15th century in the mirror of the language analysis of the chosen charters - Owsiński, Piotr A. (Acta Universitatis Lodziensis. Folia Germanica, 2018)
The article hereunder presents the language analysis of the chosen German charters from 15th century, which come from the Antiquum Registrum Privilegiorum Et Statutorum Civitatis Cracoviensis published by Stanisław Ambroży Estreicher in 1936 in Cracow. The texts of the unknown scriveners were written in the Silesian dialect, what can be proved on the basis of the way of the notation in the law.The author introduces the results of his analysis showing the Silesian characteristic features with the appropriate examples.